Սյուռեալիզմի Այվազյանական ընկալումը - Գալստյան, Ա. Վ.
In the article Ayvazian’s surrealism is presented as a supersensitive structure of art work where sensitive and intellectual self discipline and semantic development are evident. The way of his world outlook and creative reproduction is contemplation which leads from deep feelings and perceptions to surreal meditation. Supernatiral has its constant place in Ayvazian`s works entirely sensible perceptions with their life content of reproduction as well. В статье сюрреализм Айвазяна представлен как тип художественного произведения с сверхчувствительной структурой, в котором отражена чувствительная и интеллектуальная организованность и осмысленность. Его мировосприятие и путь творческого восприятия направляет к сюреалистическому мышлению. Сверхестественное имеет свое неизменное место в произведениях Айвазяна вместе со своим однозначно здоровым восприятием и живостью воспроизведенного мышления.
Keywords: Գրականագիտություն